More Than a Face: Beyond Community - Madokoro, Laura (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2024)
Based on the making of a public-facing virtual exhibit titled More Than a Face, this article explores the entangled relationship between identity, academic research, and community. In tracing the origins and conceptual frameworks that shaped the development of this exhibit, the author reflects on lessons learned from this project and on how these intersect with initiatives around equity, diversity, and inclusion (EDI) in the Canadian academic context. Rather than taking the subject of “Asian Canadian history” as a given, this article combines a scholarly inquiry into the making of the More Than a Face exhibit with personal reflections to consider the relationships that researchers have with communities and academic categories of identity and belonging.